Wilfrid Sellars and twentieth-century philosophy - Brandt, Stefan L. 1964-; Breunig, Anke (Routledge studies in American philosophy, 2021)
"This collection features fourteen original essays, divided into three thematic sections, which explore the work of Wilfrid Sellars in relation to other twentieth-century thinkers. Section I analyzes Sellars's thought in light of his influential predecessors, namely Ludwig Wittgenstein, Rudolf Carnap, C.I. Lewis, Richard Hönigswald, John Cook Wilson, and Kazimierz Ajdukiewicz. The second group of essays explores from different perspectives Sellars's place within the analytic tradition, including the extent of his identification with analytic Kantianism and analytic pragmatism. The book's final section extracts some of the most significant lessons Sellars's work has to offer for contemporary philosophy. These chapters address his views on inference, his views on truth and its connection to recent discussions about truth-relativism and truth-pluralism, his conception of self-knowledge, and his theory of perceptual experience"--